The Effect of Service Quality and Price on Customer Satisfaction of Grabbike Online Transportation Services in Cimahi City - Rosadi, Andri Asoka Sidantara; Istiqomah, Noni Zahwa Nur; Nurfadilah, Meisya Ayu (Jurnal EMT KITA, 2023)
The main thing that must be considered by the company to win the competition is to provide satisfaction to consumers through providing good service quality and competitive prices. This study aims to determine the effect of product quality and price on consumer satisfaction of GrabBike Online transportation in Cimahi City. The population in this study is GrabBike online transportation service users in Cimahi City with a sample of 97 people. Sampling is done by purposive sampling technique. The results of research through descriptive analysis show that the quality of service, price and customer satisfaction in the category is very good. The analysis technique used is linear regression analysis. Associative testing shows the effect of service quality affects customer satisfaction by 25.6%, the effect of price on consumer satisfaction by 41.5%. And the amount of influence of service quality and price on customer satisfaction is 67.1% while the remaining 32.9% is influenced by other variables that are not studied.